To simplify the expression \((r-1)(r^2 - 2r + 3)\), we'll distribute \(r-1\) to each term in the polynomial \(r^2 - 2r + 3\).
-
Multiply \(r\) by each term in \(r^2 - 2r + 3\):
- \(r \cdot r^2 = r^3\)
- \(r \cdot (-2r) = -2r^2\)
- \(r \cdot 3 = 3r\)
So, \(r(r^2 - 2r + 3) = r^3 - 2r^2 + 3r\).
-
Multiply \(-1\) by each term in \(r^2 - 2r + 3\):
- \(-1 \cdot r^2 = -r^2\)
- \(-1 \cdot (-2r) = 2r\)
- \(-1 \cdot 3 = -3\)
So, \(-1(r^2 - 2r + 3) = -r^2 + 2r - 3\).
-
Now, combine the results from steps 1 and 2: \[ r^3 - 2r^2 + 3r - r^2 + 2r - 3 \]
Combine like terms:
- \(r^3\)
- \(-2r^2 - r^2 = -3r^2\)
- \(3r + 2r = 5r\)
- \(-3\)
So, combining everything gives us: \[ r^3 - 3r^2 + 5r - 3 \]
Thus, the simplified polynomial expression is: \[ r^3 - 3r^2 + 5r - 3 \]
In the format requested: ___r^3 + __r^2 + ___r + ___ would be:
- \(1\) for \(r^3\)
- \(-3\) for \(r^2\)
- \(5\) for \(r\)
- \(-3\) (the constant term)
So, the final answer is: 1, -3, 5, -3